2000
DOI: 10.1097/00001610-200003000-00003
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Inflammatory Bowel Disease on Adolescents

Abstract: Adolescence is a time of profound change for individuals. It is a period that witnesses biologic, social, and psychological change in the individual as well as role changes within the family and peer groups. Compounding these difficult transitions with the onset of inflammatory bowel disease leads to additional problems with adolescence adjustment. In the limited studies that have addressed the adolescent and inflammatory bowel disease, several key concepts emerge that point to ways for successfully dealing wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Unauthorized reproduction of this article is prohibited share personal experiences and information related to their condition. This is unsurprising, as the challenges associated with IBD can have a particularly profound effect on adolescents and young adults, disrupting both their personal and social development and restricting their life aspirations (Brydolf & Segesten, 1996;Daniel, 2002;Decker, 2000). For example, similar to the findings of Perron (2002), this study found that communication in the sample of messages was largely driven by a desire to seek and exchange information or advice.…”
Section: Discussionmentioning
confidence: 58%
“…Unauthorized reproduction of this article is prohibited share personal experiences and information related to their condition. This is unsurprising, as the challenges associated with IBD can have a particularly profound effect on adolescents and young adults, disrupting both their personal and social development and restricting their life aspirations (Brydolf & Segesten, 1996;Daniel, 2002;Decker, 2000). For example, similar to the findings of Perron (2002), this study found that communication in the sample of messages was largely driven by a desire to seek and exchange information or advice.…”
Section: Discussionmentioning
confidence: 58%
“…As a result, the interest in the influence of disease and treatment on the course of life of these patients has intensified [1]. Research on long-term effects of having a chronic illness during the transition from adolescence to adulthood is relatively new and, with regard to digestive disorders, often involves inflammatory bowel disease (IBD) patients [2][3][4][5]. Generally, these studies address the effects of IBD on the quality of life of children and adolescents, such as the impact on social functioning (family, friends), physical functioning (body complaints, motor functioning), and psychological functioning (depression, anxiety).…”
Section: Introductionmentioning
confidence: 99%
“…Among other gastrointestinal symptoms, IBD is usually accompanied by diarrhea, abdominal pain, weight loss, and anemia (Baldassano & Picolli, 1999). In addition to these symptoms, adolescents may exhibit a growth failure and delayed puberty (Baldassano & Picolli, 1999;Decker, 2000). In managing IBD, often medical and nutritional therapy and sometimes surgery is necessary.…”
Section: Discussionmentioning
confidence: 99%